Low impact development modeling to manage urban storm water runoff and restore predevelopment site hydrology - Simpson, Matthew G., author; Roesner, Larry A., advisor; Grigg, Neil S., committee member; Glick, Scott, committee member (Colorado State University. Libraries, 2010)
The hydrologic effects of urban development have been documented for some time. Urban streams experience dramatic changes to their natural flow regime, which is mostly due to the increased rate and volume of runoff. Conventional stormwater management focuses on peak rate control through the use of detention and retention basins while paying little attention to the increased volume of urban runoff. Low Impact Development (LID) is a land planning and stormwater management approach that seeks to control runoff as close as possible to its source. LID practices take advantage of natural processes, such as infiltration, to reduce the rate and volume of runoff while improving water quality at the same time. It is hypothesized that LID can be used to restore the predevelopment hydrology to a site. This thesis investigates if LID can be used exclusively to meet stormwater requirements and secondly whether LID can maintain the predevelopment site hydrology. In order to examine if LID can restore predevelopment site hydrology, an EPA SWMM model was created based upon a proposed development in Fort Collins, CO. Several different scenarios were evaluated including: rainfall from Fort Collins, CO and Atlanta, GA; a high and a low infiltration soil; and BMPs with partial infiltration (with underdrain) and with full infiltration (without underdrain). The amount of LID in each model was increased until predevelopment peak flow rates and water balance were met; this was accomplished using design storm simulations. Each model was then analyzed with a continuous simulation using historic rainfall data from both locations. The LID BMPs that were modeled include grassed swales, rain gardens, infiltration trenches, and permeable pavement. Finally, a cost review of the LID designs was performed to explore the financial practicality of LID. The results show that LID can restore predevelopment site hydrology, but the amount of LID required is substantial. However, the cost review shows that the extra LID expense could be recovered in certain locations through development of the detention pond land which is no longer needed.
Department Head: Luis A. Garcia.